Resposta:
Explicação passo a passo:
[tex]a)[/tex]
[tex]x-y=5-(-4)=5+4=9[/tex]
[tex]b)[/tex]
[tex]3x-a=3.(2)-6=6-6=0[/tex]
[tex]c)[/tex]
[tex]2x+m=2.(-1)+(-3)=-2-3=-5[/tex]
[tex]d)[/tex]
[tex]8x+2b=8.(3)+2.(-5)=24-10=14[/tex]
[tex]e)[/tex]
[tex]7a-3c=7.(-6)-3.(-5)=-42+15=-27[/tex]
[tex]f)[/tex]
[tex]m+n=-1+5=+4[/tex]
[tex]g)[/tex]
[tex]3a+2b-c=3.(5)+2.(3)-1=15+6-1=21-1=20[/tex]
[tex]h)[/tex]
[tex]m-2a=3-2.(-5)=3+10=13[/tex]
[tex]i)[/tex]
[tex]2z+2w+2k=2.(z+w+k)=2.(5+6+7)=2.18=36[/tex]
[tex]j)[/tex]
[tex]9x+12y-3a=9.(2)+12.(3)-3.(4)=18+36-12=42[/tex]
[tex]k)[/tex]
[tex]a^{2}+2=5^{2} +2=25+2=27[/tex]
[tex]l)[/tex]
[tex]b^{2} -3=(-3)^{2} -3=9-3=6[/tex]